PERBANDINGAN JARAK PENYINARAN DAN KETEBALAN BAHAN TERHADAP KEKERASAN PERMUKAAN RESIN KOMPOSIT TIPE BULK FILL - Razibi, Nor Diane; Ichrom Nahzi, Muhammad Yanuar; Puspitasari, Dewi (FKG Unlam, 2017)
Background: The polymerisation process is a process of polymer formation of a combination of several monomers. This is due to the incomplete polymerization, which affects the consistency and durability of the composite resin in the oral cavity. The maximum surface can result in composite resin are not able to withstand the pressure generated during mastication it can undergo cracking (rupture) or off the tooth. Purpose: To compare the material thickness and curing light distance of bulk-fill composite resin to determine itsâ surface consistency. Method: Laboratorium experimental study with a post-test only with control group design. A total of 63 composite resin pieces were used as samples and divided into 9 treatment groups with different curing light distance (0 mm, 2 mm, 5 mm) and thickness (2 mm, 4 mm, 6 mm). Data were analyzed with One-Way ANOVA with a significance value of 0,000 (p<0,05). Post-Hoc Tuckey analysis with a p(<0,05) was used to determine the difference between two groups. Result: Post Hoc Tuckey analysis resulted in a significant value (p<0,05), which shows that there is a significant difference between each group and in the result show group with the thickness 2 mm and light distance 0 mm was the highest score. Conclusion: There is a comparison between curing light distance and material thickness towards surface consistency of Bulk Fill Composite Resin with thickness 2 mm and 4 mm with curing light distance 0 mm and 2 mm.